Fiber optic probe of free electron evanescent fields in the optical frequency range - So, Jin-Kyu (2014)
We introduce an optical fiber platform which can be used to interrogate proximity interactions between free-electron evanescent fields and photonic nanostructures at optical frequencies in a manner similar to that in which optical evanescent fields are sampled using nanoscale aperture probes in scanning near-field microscopy. Conically profiled optical fiber tips functionalized with nano-gratings are employed to couple electron evanescent fields to light via the Smith-Purcell effect. We demonstrate the interrogation of medium energy (30–50 keV) electron fields with a lateral resolution of a few micrometers via the generation and detection of visible/UV radiation in the 700–300 nm (free-space) wavelength range.